Bath Smelting In The Noranda Process Reactor And The El Teniente Converter Compared - Cameron Hams (The Minerals, Metals and Materials Society, 1999)
Noranda's Process Reactor and Codelco's Teniente Converter are physically similar vessels, which leads to the commonly held misconception that the two processes are the .same. However, notable differences in chemistry, operating philosophy, and construction make them quite dissimilar. This paper compares and contrasts the Noranda Reactor and the Teniente Converter, and attempts to explain some of the apparent differences in behaviour and performance. The results of a worldwide survey of most operating Noranda Reactors and Teniente Converters, along with those processes that have ceased operation or are planning to be started-up in the future, are presented.